Playing America: An Introduction to American Culture through Video Games - Fuchs, Michael (Gamevironments, 2019)
This research report sketches one of our current projects - a textbook which approaches America (an imaginative construct more so than a geographic location) through video games. Thus, the intended outcome of this project is a ready-to-use primer to the key principles, myths, and beliefs that constitute America explained through the most relevant medium of the early twenty-first century - video games. Driven by the idea that the interactivity specific to video games facilitates student engagement, our textbook suggests a novel approach to engage with and understand both American Studies and American culture.